2016
DOI: 10.2460/javma.248.7.795
|View full text |Cite
|
Sign up to set email alerts
|

Safety and clinical effectiveness of a compounded sustained-release formulation of buprenorphine for postoperative analgesia in New Zealand White rabbits

Abstract: Sustained-release buprenorphine administered SC at 0.12 mg/kg was at least as effective as regular buprenorphine in providing analgesia for rabbits following orthopedic surgery without any major adverse effects. This sustained-release formulation represents an important alternative for rabbit analgesia with potential to improve rabbit welfare over existing analgesic standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 10 publications
0
19
1
Order By: Relevance
“…Different formulations of compounded SR‐buprenorphine have been used in several laboratory, companion, and farm animal species, with variable results and effects. In many of these studies, the authors reported different types of skin lesions most likely due to reaction to the vehicle (Carbone et al., ; Catbagan et al., ; Clark et al., ; DiVincenti et al., ; Foley et al., ; Molter et al., ; Nunamaker et al., , ; Thiede et al., ). Additionally, reports of inconsistent systemic absorption following use of this formulation have been described (Dooley et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Different formulations of compounded SR‐buprenorphine have been used in several laboratory, companion, and farm animal species, with variable results and effects. In many of these studies, the authors reported different types of skin lesions most likely due to reaction to the vehicle (Carbone et al., ; Catbagan et al., ; Clark et al., ; DiVincenti et al., ; Foley et al., ; Molter et al., ; Nunamaker et al., , ; Thiede et al., ). Additionally, reports of inconsistent systemic absorption following use of this formulation have been described (Dooley et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in mice and rats demonstrated an analgesic effect of 48–72 hr duration following a single s.c. injection of different SR‐buprenorphine compounds (Carbone, Lindstrom, Diep, & Carbone, ; Chum et al., ; Clark, Clark, & Hoyt, ; Foley, Liang, & Crichlow, ; Healy et al., ; Jirkof, Tourvieille, Cinelli, & Arras, ; Kendall et al., ). Similar SR‐buprenorphine compounds have been used in dogs (Nunamaker et al., ; Tomas, Bledsoe, Wall, Davidson, & Lascelles, ), cats (Catbagan, Quimby, Mama, Rychel, & Mich, ; Enomoto et al., ; Johnson et al., ), rabbits (DiVincenti, Meirelles, & Westcott, ), Göttingen minipigs (Thiede et al., ), guinea pigs (Smith, Wegenast, Hansen, Hess, & Kendall, ), sheep (Gatson, Pablo, Plummer, & Granone, ; Walkowiak & Graham, ; Zullian et al., ), alpaca (Dooley et al., ), elephant seals (Molter et al., ), and macaques (Nunamaker et al., ). However, the SR‐buprenorphine formulations used in these studies were either unknown or compounded products and, in most of these studies, the authors reported skin lesions at the site of injections, ranging from simple s.c. nodules to abscesses, open wounds, and necrotic lesions likely caused by the viscosity of the product or the formulation matrix (Carbone et al., ; Catbagan et al., ; Clark et al., ; DiVincenti et al., ; Foley et al., ; Molter et al., ; Nunamaker et al., , ; Thiede et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moderate to severe inflammatory reactions have been reported for SC implants of polymer-opiate constructs [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%